Assessment of alcohol and psychotropic drug use among old-age psychiatric patients in Norway: Experiences of health professionals. Issue 3 (June 2017) - Johannessen, Aud; Engedal, Knut; Helvik, Anne-Sofie
Background: Increased awareness among health professionals regarding older people's alcohol and prescribed psychotropic drug use may be beneficial for reducing their unhealthy consumption among elderly. Aim: This study explores how health professionals experienced their participation in a study in which they collected data on alcohol and psychotropic drug use among patients treated in old-age psychiatry departments and, subsequently, how they experienced their work day after the study ended. Method: Focus-group and individual interviews with 15 professionals in specialist psychiatric hospitals were performed in 2016. The data were analysed using content analysis. Results: Two themes emerged from the data: the informants' "experiences with participation" and "consequences of participation". These themes described how the informants had experienced their participation in the study and whether these experiences subsequently affected their work routines. The first theme included two subthemes: "approaching the topic" covered the challenges and "applying assessment scales" described the participants' opinions about the scales. Two subthemes were included in the second theme: "increasing knowledge", which covered their reflections on new knowledge; and "influencing work routines", which described their new approach to the topic. Conclusion: Study participation positively affected the informants' work routines regarding alcohol and psychotropic drug use. The results of this study may contribute to a better understanding, development, and organization of services for people with increased substance use and thus may more holistically promote the health of older people.